2016
DOI: 10.1097/bcr.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Burn Center Volume on Mortality in a Pediatric Population

Abstract: The effect of burn center volume on mortality has been demonstrated in adults. The authors sought to evaluate whether such a relationship existed in burned children. The National Burn Repository, a voluntary registry sponsored by the American Burn Association, was queried for all data points on patients aged 18 years or less and treated from 2002 to 2011. Facilities were divided into quartiles based on average annual burn volume. Demographics and clinical characteristics were compared across groups, and univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
7
20
1
Order By: Relevance
“…( 1 , 4 , 7 ) Mortality among burned patients has decreased in previous decades, and recent studies have shown a correlation between mortality and BBS > 60%. ( 4 , 7 , 16 , 17 ) This same association was found in our study, as we observed more significant mortality in patients with a BBS > 50%.…”
Section: Discussionsupporting
confidence: 91%
“…( 1 , 4 , 7 ) Mortality among burned patients has decreased in previous decades, and recent studies have shown a correlation between mortality and BBS > 60%. ( 4 , 7 , 16 , 17 ) This same association was found in our study, as we observed more significant mortality in patients with a BBS > 50%.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings of Morrow et al, we did find an increased risk of mortality among children under the age of 4 who sustained burn sizes between 30% and 60% TBSA [7]. Hodgman et al identified a similar trend in a recent analysis of the National Burn Repository [10]. However, this trend was not consistent for patients with small and large burns.…”
Section: Discussionsupporting
confidence: 84%
“…Over the 35 years of the study period, the mortality rate following a thermal injury among children admitted to Parkland was low at 2.5%; although this is higher than reported in several recent analyses of a pediatric subset of the National Burn Repository, which found rates of less than 1% [6,10]. However, we did see a significant decrease in mortality over time, with the rate approaching 1% in the last 5 years of analysis.…”
Section: Discussioncontrasting
confidence: 67%
“…9,17 Estimations of the median lethal burn size (Lethal Area, 50%; LA50) LA 50 of a geriatric population range from 27.8% to 30.0% TBSA; this burn size would equate to a minimum Baux score of 92.8 to 95, which is quite similar to our cutoff point of 93 for increased risk of mortality. 7,18 However, among burn patients, there is a complex interplay between a patient's age and a decreased ability to adapt to stressors and the physiologic sequelae of the burn itself.…”
Section: Discussionmentioning
confidence: 94%
“…6 Unfortunately, the Baux score (or revised Baux score) has generally been studied using data sets that are dated, or inclusive of all age groups, effectively limiting their applicability to the geriatric subset. [7][8][9][10] Most importantly, despite the simplicity of the Baux score, its predictive ability has never been packaged as a simple and approachable decision aid.…”
mentioning
confidence: 99%